CAUSAL RELATIONSHIP AMONGST CORPORATE LONG-TERM FINANCING DECISIONS: EMPIRICAL EVIDENCE OF LISTED NIGERIAN MANUFACTURING FIRMS - Jeremiah Babajide OPALEKE (Malete Journal of Accounting and Finance, 2023)
Considering the effects of the COVID-19 pandemic amongst other present global economic challenges on the growing Nigerian manufacturing firms, this study is conducted to offer useful information to corporate executives and economic policy makers on the importance of the relationship between a firm’s investment, financing and dividend payout choices (the corporate long-term financial decisions). Specifically, this study sought to ascertain if and how a firm’s capital investment, finance and dividend payout decisions inform one another. To make the study eclectic, Agency theory of corporate and financial management and the Panel Granger’s causality model were adopted as the study’s theoretical frameworks. To achieve the aim of this study, a sample of 35 stratifiedly selected Nigerian manufacturing firms on the Nigerian Stock Exchange (NSE) between the periods of 1990-2020 (30 years) were examined, in the quest to fill sectoral and periodical gaps found in the extant empirical studies. The adopted methodology is quantitative and it is anchored on statistical and Panel Granger’s causality techniques. The trio of capital investment, financing and dividend payout is the study’s dependent and controllable variables, which are measured by the sampled firms’ fixed assets; addition of equities and debts; and the declared dividend payments for the periods covered respectively. The data employed were of unbalanced panel that is purely secondary. In all, the study revealed through the conducted Granger’s causality test that a bi-directional type of causation exists between the trio of capital investment, financing and dividend payout decisions. And based on this empirical evidence, the study concludes that a firm’s capital investment, its finance and dividend payout decisions causal relates and influence one another. Following this conclusion, the study recommends to concerned corporate and governmental decision makers that at all times the multiplier implications surrounding any of the three examined long-term financing decisions (i.e. capital investment, finance and dividend payout) on one another, and their joint effects on the firm’s, sectoral and economic stability, especially when seeking competitive edge and growth should be considered